The Influence Of Digital Marketing, Word Of Mouth, Perception Of Job Opportunities On Participant Animo With Brand Engagement, Awareness, Image As Mediators - Abdiarta, Anak Agung Gede; Mahyuni, Luh Putu (UNIVERSITAS PAKUAN, 2023)
Several factors that encourage prospective students to determine the choice of continuing their studies are: Digital Marketing, Word of Mouth, Perception of Job Opportunities, Brand Engagement, Brand Awareness, Brand image which in the current digital era really determines the interest of prospective students. The marketing communication strategy carried out by the LPK Mediterranean Bali Campus is aimed at increasing visits due to the interest of prospective students themselves. Just like the perception of buying interest. The minimum number of respondents that must be obtained is 100 respondents. The sampling technique used in this research is purposive sampling, so that in determining the sample, certain criteria are required. The data used in this research is quantitative data. Quantitative data is data in the form of numbers. The data collection method used in this research was through a questionnaire. The result of the research are digital marketing on brand engagement, brand awareness, brand image has positive and significant results. The brand engagement, brand awareness, brand image, digital marketing has a positive and significant influence on student enthusiasm. Word of mouthon students' enthusiasm has a negative and significant influence. Perception of job opportunities on student interest. The results of this research can be used as a reference for developing more appropriate, effective and efficient strategies in improving the institutional brand while increasing student interest.